2013
DOI: 10.1111/j.1447-0756.2012.02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional power Doppler and endometrial volume as predictors of malignancy in patients with postmenopausal bleeding

Abstract: 3D-PDA measurements may be useful for distinguishing between benign endometrial lesions and endometrial carcinoma in patients with postmenopausal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This is partly due to the situation of blood flow and VOCAL program which applies a rotational method. Previous studies have shown that VI, FI, and VFI could be a helpful tool to detect the malignancies, such as endometrial neoplasms and ovarian tumor [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is partly due to the situation of blood flow and VOCAL program which applies a rotational method. Previous studies have shown that VI, FI, and VFI could be a helpful tool to detect the malignancies, such as endometrial neoplasms and ovarian tumor [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further 24 studies were excluded: two studies did not use the VOCAL method; 14 studies included only patients with previous diagnosis of carcinoma; four studies included premenopausal and postmenopausal women and data could not be stratified for menopausal status; in three studies it was not possible to retrieve data to make a 2×2 table to calculate true positive, true negative, false positive, and false negative cases; and one study was a retrospective study using the same data of another included study. The remaining eight [16][17][18][19][20][21][22][23] studies were ultimately included in the present meta-analysis. No additional studies from references cited in these eight studies were found.…”
Section: Search Resultsmentioning
confidence: 99%
“…They concluded that power Doppler analysis can contribute to a correct diagnosis of endometrial cancer in women with postmenopausal bleeding. Makled et al [ 13 ] also concluded that 3D power Doppler measurements may be useful for distinguishing between benign endometrial lesions and endometrial carcinoma in women with postmenopausal bleeding.…”
Section: Discussionmentioning
confidence: 99%